Interactive simulators to study the passive properties of the axon and the dendritic tree - Reyes Lazalde, Arturo; Pérez-Bonilla, M. E.; Fuchs-Gómez, O. L.; Reyes-monreal, M. (Revista Mexicana de Ingenieria Biomedica, 2012)
In recent years, interactive media and tools, such as scientific simulators and simulation environments or dynamic data visualizations, have became established methods in the neural, medical, physiological and biophysical sciences. This article presents two simulators designed and developed for the study of the passive properties of the axon and dendritic tree: HR2 and Rall1. The HR2 is an interactive program that reproduces the classic experiments of Hodgkin and Rushton (1946) to determine the electrical constants of a crustacean nerve fiber. Rall1 is an interactive program that enables the study of the Rall model by reducing the dendritic tree to an electrically equivalent cylinder. With these simulators, students can etermine the time constant and electrotonic length in axons and dendrites. These simulators are powerful tools for exploring and analyzing the complexity of the passive properties in neural information processing.